2017
DOI: 10.1149/2.0381712jss
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric Pressure Plasma Enhanced Spatial ALD of ZrO2for Low-Temperature, Large-Area Applications

Abstract: High permittivity (high-k) materials have received considerable attention as alternatives to SiO 2 for CMOS and low-power flexible electronics applications. In this study, we have grown high-quality ZrO 2 by using atmospheric-pressure plasma-enhanced spatial ALD (PE-sALD), which, compared to temporal ALD, offers higher effective deposition rates and uses atmospheric-pressure plasma to activate surface reactions at lower temperatures. We used tetrakis(ethylmethylamino)zirconium (TEMAZ) as precursor and O 2 plas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 59 publications
0
14
0
Order By: Relevance
“…[16,17] This makes sALD well-suited for highly precise, high throughput, and in-line material processing over large areas, e.g., roll-to-roll and sheet-to-sheet sALD. [18][19][20] ALD relies extensively on the underpinning reactive chemistry of precursors. As such the development of new and more reactive precursors is an essential method of improving GPC and overall deposition rate.…”
Section: Introductionmentioning
confidence: 99%
“…[16,17] This makes sALD well-suited for highly precise, high throughput, and in-line material processing over large areas, e.g., roll-to-roll and sheet-to-sheet sALD. [18][19][20] ALD relies extensively on the underpinning reactive chemistry of precursors. As such the development of new and more reactive precursors is an essential method of improving GPC and overall deposition rate.…”
Section: Introductionmentioning
confidence: 99%
“…We note that in our top‐gated SA TFTs, a low‐temperature PECVD SiO 2 gate dielectric is deposited on top of the sALD semiconductor layer, while the hydrogen doping of the semiconductor at the contact regions is mainly determined during the SiN intermetal dielectric deposition. We therefore expect that the observed bias stress behavior of sALD IGZO TFTs is not inherent to the sALD deposited material and can be further improved by modifications in the TFT stack process flow as well as by using sALD‐deposited dielectrics, in order to better control hydrogen content in the TFT stack. This is indeed demonstrated in the case of the sALD buffer layer, where it can be seen from Figure that both the positive and the negative bias stresses are improved with respect to the PECVD SiO 2 buffer layer.…”
Section: Resultsmentioning
confidence: 99%
“…Intrinsic metal oxides HfO 2 [11] Al 2 O 3 [14-16, 19-21, 26, 31, 35-50] ZnO [18,36,39,45,46,[51][52][53][54][55][56][57][58][59][60][61][62][63][64][65][66][67] SnO x [68,69] TiO 2 [14,18,[70][71][72] Cu 2 O [46,73,74] Nb 2 O 5 [71] NiO x [91] ZrO 2 [92,93] MoO x [94] Doped SALD has also been used for LEDs, in some cases to deposit active ZnO layers for polymer and hybrid perovskite-based diodes [54,76], and in another case using Al 2 O 3 as permeation barrier for flexible organic LEDs [49]. Other authors have also demonstrated the suitability of SALD for depositing barrier and encapsulation layers both on plastic and paper substrates [14,31,40,48].…”
Section: Materials Referencesmentioning
confidence: 99%